Improved node localization algorithm for wireless sensor network - ZENG Fan-zi; SUN Zheng-zhang; LUO Juan; LI Ren-fa (Tongxin xuebao)
An location algorithm called MCBN（Monte Carlo localization boxed using non-anchor） was proposed, which is based on the Monte Carlo localization algorithm. In this algorithm, the smallest anchor box is constructed by the an- chor nodes within two hops in the network and the non-anchor nodes with minimum credit value and known coordinates, which leads to a shrank box where the sample and filter is more efficient to node location compared to the MCL and MCB. Simulation results show that MCBN has better performance than MCL and MCB in the node localization accuracy and energy consumption.